2011
DOI: 10.1111/j.1574-695x.2011.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Preterm and term neonates transplacentally acquire IgG antibodies specific to LPS fromKlebsiella pneumoniae, Escherichia coliandPseudomonas aeruginosa

Abstract: High incidences of Gram-negative bacteria are found in neonatal nosocomial infections. Our aim was to investigate placental transmission of immunoglobulin G (IgG) reactive with lipopolysaccharide from Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli O111, O6 and O26. The total and lipopolysaccharide-specific IgM and IgG were determined in 11 maternal/umbilical-cord sera aged ≤33 weeks (GI); 21 aged >33 and <37 weeks (GII); and 32 term newborns (GIII). The total and lipopolysaccharide-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…It was reported by Michaux et al [44] that total IgG concentrations in cord sera tend to be lower than in their mothers when total IgG levels in maternal serum reached 15 g/L. This is in agreement with other works that have demonstrated significant negative correlations between maternal levels of IgG and placental transfer ratios to the neonate for both total IgG and, interestingly, IgG specific to measles, LPS and other antigens [41, 45, 46]. …”
Section: Placental Transport Of Igg Depends On Maternal Levelssupporting
confidence: 89%
See 2 more Smart Citations
“…It was reported by Michaux et al [44] that total IgG concentrations in cord sera tend to be lower than in their mothers when total IgG levels in maternal serum reached 15 g/L. This is in agreement with other works that have demonstrated significant negative correlations between maternal levels of IgG and placental transfer ratios to the neonate for both total IgG and, interestingly, IgG specific to measles, LPS and other antigens [41, 45, 46]. …”
Section: Placental Transport Of Igg Depends On Maternal Levelssupporting
confidence: 89%
“…Accordingly, in a recent study, van den Berg et al [54] found significantly lower transplacental transmission of IgG in preterm infants (<32 weeks) than in full-term infants for antibodies against diphtheria, tetanus, pertussis, Haemophilus influenza type b (Hib), and Neisseria meningitides serogroup C. In agreement with these data, Silveira Lessa et al [46] evaluated the placental transfer ratios of IgG antibodies reactive with Klebsiella , Pseudomonas, and E. coli O111, O26, and O6 lipopolysaccharides and showed lower anti-LPS IgG transfer ratios in preterm groups (<33 weeks and >33 weeks) as compared with term ones (>37 weeks).…”
Section: Igg Transport Depends On Gestational Agementioning
confidence: 68%
See 1 more Smart Citation
“…Premature neonates are even more susceptible to infections due to several factors, including immature mechanical barriers, limited neutrophils function, low plasma concentrations of specific antibodies, low activities of the complement system proteins and poor cooperation between T and B lymphocytes. This favors bacterial translocation across the intestinal epithelium and dissemination to other organs and tissues, thereby increasing the risk of systemic infections and potential for sepsis 23,24,25 .…”
Section: Discusionmentioning
confidence: 99%
“…These are the receptors responsible for transplacental transport of maternal serum IgG antibodies to the developing fetus. Several past studies have observed that an increase in maternal total IgG can lead to lower transplacental transfer ratios for IgG antibodies specific to anti-tetanus [36], anti-measles [37, 38], and anti-lipopolysaccharide from E. coli [39]. Consistency of arsenic’s effect on total immunoglobulin (Ig) levels has also been observed among non-pregnant adults, who demonstrate measurably elevated serum total IgG as well as total IgA and IgE [20].…”
Section: Arsenic Exposure and Immune Responsesmentioning
confidence: 99%